Impact of neoadjuvant FLOT treatment of advanced gastric and gastroesophageal junction cancer following surgical therapy - Paszt, Attila; Simonka, Zsolt; Budai, Krisztina; Horvath, Zoltan; Erdos, Marton; Vas, Marton; Ottlakan, Aurel; Nyari, Tibor; Szepes, Zoltan; Uhercsak, Gabriella; Maraz, Aniko; Torday, Laszlo; et al. (Frontiers in Surgery, 2023)
Introduction: Therapeutic treatment for advanced-stage (T2-T4) gastroesophageal junction (GEJ) and gastric cancer involves neoadjuvant chemotherapy with subsequent surgical intervention. Method: Neoadjuvant oncological treatment for GEJ and gastric cancer previously consisted of the intravenous administration of epirubicin, cisplatin and fluorouracil (ECF) or epirubicin, cisplatin and capecitabine (ECX) combination (Group 1). The new protocol (FLOT, F: 5-FU, L: leucovorin, O: oxaliplatin, T: docetaxel), included patients with resectable GEJ and gastric cancer who had a clinical stage cT2 or higher nodal positive cN+ disease (Group 2). Between 31 December 2008 and 31 October 2022, the effect of different oncological protocols in terms of surgical outcomes in cases of T2–T4 tumours were retrospectively evaluated. Results of randomly assigned patients from the earlier ECF/ECX protocol (n = 36) (Group 1) and the new FLOT protocol (n = 52) (Group 2) were compared. Effect of different neoadjuvant therapies on tumour regression, types of possible side effects, type of surgery, and oncological radicality of surgical procedures were analysed. Results: When comparing the two groups, we found that in case of the FLOT neoadjuvant chemotherapy (Group 2, n = 52), complete regression was achieved in 13.95% of patients, whereas in the case of ECF/ECX (Group 1, n = 36), complete regression occurred in only 9.10% of patients. Furthermore, in the FLOT group, the mean number of lymph nodes removed was slightly higher (24.69 vs. 20.13 in the ECF/ECX group). The occurrence of diarrhea was significantly higher in the FLOT group (p=0.006). Leukopenia and nausea occurred more commonly with the old protocol (Group 1). The rate of neutropenia was lower following FLOT treatment (p = 0.294), with the lack of grade II and III cases. Anaemia occured at a significantly higher rate (p = 0.036) after the ECF/ECX protocol. Conclusions: As a result of the FLOT neoadjuvant oncological protocol for advanced gastro-esophageal junction and gastric cancer, the rate of complete tumour regression increased significantly. The rate of side effects was also appreciably lower following the FLOT protocol. These results strongly suggest a significant advantage of the FLOT neoadjuvant treatment used before surgery.